Ocular complications of tumour necrosis factor alpha inhibitors. (11th May 2019) - Kowalski, Tanya; Mack, Heather G
Abstract : Tumour necrosis factor alpha inhibitors are a relatively recent development and are becoming increasingly common in the management of many chronic inflammatory conditions such as rheumatoid arthritis, inflammatory bowel disease, ankylosing spondylitis and juvenile idiopathic arthritis. However, their ocular side effect profile is incomplete and poorly recognised, with mostly anecdotal cases reported in the literature. In this report we review the literature regarding ocular side effects associated with tumour necrosis factor alpha blockade.